2013
DOI: 10.1007/978-1-62703-478-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of In Vitro Maintained and Matured Populations: Potential Barriers to Engraftment of Human Pluripotent Stem Cell Derivatives

Abstract: The potential to develop into any cell type makes human pluripotent stem cells (hPSCs) one of the most promising sources for regenerative treatments. Hurdles to their clinical applications include i) formation of heterogeneously differentiated cultures, ii) the risk of teratoma formation from residual undifferentiated cells, and iii) immune rejection of engrafted cells. The recent production of human isogenic (genetically identical) induced PSCs (hiPSCs) has been proposed as a “solution” to the histocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…This phenomenon might be due to residual pluripotent gene expression in the tumors derived from autologous iPSCs, as described (Dhodapkar et al, 2010; Tang et al, 2013). However, we did not detect residual OCT4 expression in teratoma tissues despite ongoing lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This phenomenon might be due to residual pluripotent gene expression in the tumors derived from autologous iPSCs, as described (Dhodapkar et al, 2010; Tang et al, 2013). However, we did not detect residual OCT4 expression in teratoma tissues despite ongoing lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 96%
“…However, the central nervous system is an immunologically protected and unique environment. Therefore, there is still a question about immunogenicity and tumorigenicity of iPSCs and their differentiated derivates when they are grafted into immunocompetent sites (Lee et al, 2013; Tang et al, 2013). Hence, there is a need to assess the safety and efficiency of iPSC-based therapies in a clinically relevant model (Kaneko and Yamanaka, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have suggested that iPSC-derived cells can be immunogenic even when donor and recipient are genetically identical 98100 . This may be due to retention of developmental antigens, acquisition of xenogenic epitopes, or expression of aberrant antigens over the course of long-term cultures used to generate iPSCs and differentiated cells 101,102 . Nonphysiologic in vitro differentiation can also alter the expression of molecules involved in immune recognition in a way that would trigger immune system reactions against the cells after transplantation, such as NK cell–mediated killing of cells expressing low levels of self MHC class I molecules 101 .…”
Section: Future Directionsmentioning
confidence: 99%
“…This may be due to retention of developmental antigens, acquisition of xenogenic epitopes, or expression of aberrant antigens over the course of long-term cultures used to generate iPSCs and differentiated cells 101,102 . Nonphysiologic in vitro differentiation can also alter the expression of molecules involved in immune recognition in a way that would trigger immune system reactions against the cells after transplantation, such as NK cell–mediated killing of cells expressing low levels of self MHC class I molecules 101 . Possible solutions to these problems include the development of mild immunosuppressive regimens (e.g., monoclonal antibodies targeting NK cells and/or T cell subsets) sufficient to induce tolerance to autologous iPSC-derived cells.…”
Section: Future Directionsmentioning
confidence: 99%